Management of cerebrospinal fluid disorders. Issue 11 (November 2018) - Ellenbogen, Jonathan R.; Mallucci, Conor
Abstract: Cerebrospinal fluid (CSF) disorders generally result in an excess volume of CSF within the neuraxis and an increase in intracranial pressure, defined as hydrocephalus. The treatment of hydrocephalus remains surgical with the aim of CSF diversion, but the best technique and the best assessment of adequacy of treatment remains undecided in many cases. While shunt insertion remains the mainstay of treatment, neuroendoscopic interventions such as endoscopic third ventriculostomy (ETV) have proven successful for specific pathological conditions. Improved understanding of CSF dynamics and hydrocephalus pathophysiology together with technological advances in neuroimaging, neuronavigation, and shunt hardware is leading to a more bespoke, patient-specific approach to this complex and multifactorial pathological entity. In this paper we discuss the basics of our current understanding in CSF physiology, the presenting signs and symptoms of hydrocephalus and the modalities best employed to diagnose it. We also discuss treatment modalities and the tailored approach required to specific CSF disorders.